2020
DOI: 10.1021/acsapm.0c00524
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Molecular Dynamics Simulations and Validation of Thermophysical Properties of Polymers for Various Applications

Abstract: Recent advances in graphics processing unit (GPU) hardware and improved efficiencies of atomistic simulation programs allow for the screening of a large number of polymers to predict properties that require running and analyzing long molecular dynamics (MD) trajectories. This paper outlines a MD simulation workflow based on GPU MD simulation and the refined optimized potentials for liquid simulation (OPLS) OPLS3e force field to calculate glass transition temperatures (T gs) of 315 polymers for which Bicerano r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 69 publications
(119 reference statements)
7
62
0
Order By: Relevance
“…77−79 It is acknowledged that MD conditions are not exactly consistent with experiments such as the MD's high cooling rate on the nanosecond time scale. 78,80−82 Nevertheless, a consistent trend between MD simulated T g and experimental observation has been demonstrated by Afzal et al 83 over 315 common polymers. To verify the reliability of our MD simulations, we also selected 100 polymers in our Data set_1 test set for MD simulations through K-means clustering (K = 100).…”
Section: (Ccccccc)cc(ccccccc)cc(ccccccc)cc-(ccccccc)cc(ccccccc)cc(ccc...mentioning
confidence: 55%
See 1 more Smart Citation
“…77−79 It is acknowledged that MD conditions are not exactly consistent with experiments such as the MD's high cooling rate on the nanosecond time scale. 78,80−82 Nevertheless, a consistent trend between MD simulated T g and experimental observation has been demonstrated by Afzal et al 83 over 315 common polymers. To verify the reliability of our MD simulations, we also selected 100 polymers in our Data set_1 test set for MD simulations through K-means clustering (K = 100).…”
Section: (Ccccccc)cc(ccccccc)cc(ccccccc)cc-(ccccccc)cc(ccccccc)cc(ccc...mentioning
confidence: 55%
“…Thus, the PCFF force field is particularly suitable for the molecular simulation of polymer’s T g value . A cooling process simulation generates the specific volume vs temperature curve, from which rubbery phase and glassy phase are identified, and their intersection gives the T g value. It is acknowledged that MD conditions are not exactly consistent with experiments such as the MD’s high cooling rate on the nanosecond time scale. , Nevertheless, a consistent trend between MD simulated T g and experimental observation has been demonstrated by Afzal et al over 315 common polymers. To verify the reliability of our MD simulations, we also selected 100 polymers in our Data set_1 test set for MD simulations through K -means clustering ( K = 100).…”
Section: Datasets Models and Methodsmentioning
confidence: 98%
“…Owing to the computational cost of predicting glass transition temperatures ( T g ) using physics-based simulations ( Afzal et al, 2021 ), we opted to use a QSPR model instead. The QSPR model was trained to predict T g based on 250 known OLED materials from the literature ( Naito and Miura, 1993 ; Fujikawa et al, 2000 ; Shirota, 2000 ; Yin et al, 2003 ; Kimura et al, 2005 ; Xu and Chen, 2005 ; Gao et al, 2007 ; Shirota and Kageyama, 2007 ).…”
Section: Methods and Principlesmentioning
confidence: 99%
“…Under such conditions, sufficient chain relaxation cannot occur, and the rubbery state acts as a glassy state. Interestingly, Afzal et al [ 33 ] found that the discrepancy between measured and calculated T g is consistent within a simulation protocol, and hence could be accounted for with proper calibration. Alternatively, the difference between experimental and computational rates could potentially be bridged using time-temperature superposition [ 24 , 31 ].…”
Section: Resultsmentioning
confidence: 99%